Cognitive Enhancement as Transformative Experience: The Challenge of Wrapping One’s Mind Around Enhanced Cognition via Neurostimulation - Tubig, Paul A. (Cambridge quarterly of healthcare ethics, 2024)
In this paper, the authors explore the question of whether cognitive enhancement via direct neurostimulation, such as through deep brain stimulation, could be reasonably characterized as a form of transformative experience. This question is inspired by a qualitative study being conducted with people at risk of developing dementia and in intimate relationships with people living with dementia (PLWD). They apply L.A. Paul’s work on transformative experience to the question of cognitive enhancement and explore potential limitations on the kind of claims that can legitimately be made about individual well-being and flourishing, as well as limit the kind of empirical work—including the authors’ own—that can hope to enlighten ethical discourse. In this paper, the authors advance the following theses: (1) it is sometimes reasonable to characterize cognitive enhancement as a transformative experience; (2) the testimonies of people intimately acquainted with dementia may still be relevant to evaluating cognitive enhancement even though cognitive enhancement may be a transformative experience; and (3) qualitative studies may still be useful in the ethical analysis of cognitive enhancement, but special attention may need to be given to how these are conducted and what kind of insights can be drawn from them.